ASSESSING GENDER INEQUALITY AND SOCIO-ECONOMIC DEVELOPMENT IN NIGERIA (1990–2022): AN ARDL MODEL APPROACH - Effiong, Charles Efefiom; Ayodele, Oluwafemi; Obot, Idopise Sunday (African Journal of Social and Behavioural Sciences, 2025)
This study aimed to investigate the impact of gender inequality on socioeconomic development in Nigeria. The study utilized secondary data from 1990 to 2022 on per capita gross domestic product and unemployment as proxies for socio-economic development as well as female-to-male labour force participation rate, female-to-male secondary enrolment, and female to-male adult mortality rate to capture gender inequality. The study made use of the Autoregressive Distributed Lag (ARDL) model based on the outcome of unit root test. The empirical result revealed that female-to-male labour force participation rate, female-to-male secondary school enrolment, and female to-male adult mortality rate is statistically significant for socioeconomic development in Nigeria. Furthermore, the result also reveals that government expenditure and technology were found to be significant determinants of socio-economic development during the study period. The adjusted R-squared of the per capita gross domestic product equation of 84 per cent is higher than that of the unemployment equation, which is 67 per cent. This implies that the explanatory power of the per capita gross domestic product equation is higher than that of the unemployment equation. The study recommends that government should ensure that the female child primary to secondary school education is made compulsory and free in all the states in Nigeria. Government should implement healthcare policies that reduce the gap between female and male adult mortality rates as well as spend more resources on research so as to discover new techniques of production in order to create employment opportunities in the economy.